1998
DOI: 10.1080/07448489809596003
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-Counter Psychotropics: A Review of Melatonin, St John's Wort, Valerian, and Kava-Kava

Abstract: Use and availability of alternative healthcare products have revived in the last few years. The prevalence of supplement use in the United States is largely unknown but is thought to be widespread. In this article, four of the common substances used to treat emotional problems are reviewed. The plant or substance description, clinical indications, evidence of therapeutic efficacy, mechanisms of therapeutic actions, dosages and regimens, different commercially available preparations, and adverse effects and tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…MEL has been evaluated as a therapeutic agent in a number of conditions, including sleep disturbance, jet lag, and metastatic cancer (Lissoni et al, 1989;Herxheimer and Petrie, 2002;Singer et al, 2003). These putative pleiotropic effects of MEL have not gone unnoticed by the dietary supplement industry: MEL is sold unregulated as a dietary supplement, and some concerns have been expressed regarding potential toxicity and drug interactions (Holliman and Chyka, 1997;Heiligenstein and Guenther, 1998). One prominent internet vendor lists 102 melatonin products under 32 separate brand names and mentions MEL in relation to such diverse conditions as jet lag, cluster headaches, lung cancer, depression, glaucoma, and epilepsy.…”
mentioning
confidence: 99%
“…MEL has been evaluated as a therapeutic agent in a number of conditions, including sleep disturbance, jet lag, and metastatic cancer (Lissoni et al, 1989;Herxheimer and Petrie, 2002;Singer et al, 2003). These putative pleiotropic effects of MEL have not gone unnoticed by the dietary supplement industry: MEL is sold unregulated as a dietary supplement, and some concerns have been expressed regarding potential toxicity and drug interactions (Holliman and Chyka, 1997;Heiligenstein and Guenther, 1998). One prominent internet vendor lists 102 melatonin products under 32 separate brand names and mentions MEL in relation to such diverse conditions as jet lag, cluster headaches, lung cancer, depression, glaucoma, and epilepsy.…”
mentioning
confidence: 99%
“…That a product is "natural" does not mean that it is either safe or effective. Many supplements are potent drugs that lack sufficient data on safety, doseresponse relationships, drug interactions, and purity 247 . It has been reported that melatonin consumption has resulted in eosinophilia in some humans taking high doses of this supplement.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of melatonin in the digestive mucosa typically exceeds that found in the blood, by up to 100 times . In most countries, including the United States of America (USA), melatonin is easily available as an over‐the‐counter oral supplement …”
Section: What Is Known and Objectivementioning
confidence: 99%